Natural Disturbance-Based Forest Management: Moving Beyond Retention and Continuous-Cover Forestry - Kuuluvainen, Timo; Angelstam, Per; Frelich, Lee; Jõgiste, Kalev; Koivula, Matti; Kubota, Yasuhiro; Lafleur, Benoit; Macdonald, Ellen (Frontiers in Forests and Global Change, 2021)
Global forest area is declining rapidly, along with degradation of the ecological condition of remaining forests. Hence it is necessary to adopt forest management approaches that can achieve a balance between (1) human management designs based on homogenization of forest structure to efficiently deliver economic values and (2) naturally emerging self-organized ecosystem dynamics that foster heterogeneity, biodiversity, resilience and adaptive capacity. Natural disturbance-based management is suggested to provide such an approach. It is grounded on the premise that disturbance is a key process maintaining diversity of ecosystem structures, species and functions, and adaptive and evolutionary potential, which functionally link to sustainability of ecosystem services supporting human well-being. We review the development, ecological and evolutionary foundations and applications of natural disturbance-based forest management. With emphasis on boreal forests, we compare this approach with two mainstream approaches to sustainable forest management, retention and continuous-cover forestry. Compared with these approaches, natural disturbance-based management provides a more comprehensive framework, which is compatible with current understanding of multiple-scale ecological processes and structures, which underlie biodiversity, resilience and adaptive potential of forest ecosystems. We conclude that natural disturbance-based management provides a comprehensive ecosystem-based framework for managing forests for human needs of commodity production and immaterial values, while maintaining forest health in the rapidly changing global environment.